2016
DOI: 10.3374/014.057.0104
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Fossil Record of Turtles of the CladePan-Kinosternoidea

Abstract: Turtles of the total clade Pan-Kinosternoidea have a relatively poor fossil record that extends back to the Late Cretaceous (Campanian). The clade is found only in North America during its early history, but dispersed to Central America no later than the Miocene and to South America no later than the Pleistocene. Ancestral pan-kinosternoids were likely aquatic, bottom-walking omnivores or carnivores that preferred low-energy freshwater habitats. The Pan-Dermatemys lineage is often recovered in more fluvial hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 73 publications
2
37
0
Order By: Relevance
“…Although the available character evidence is conflicting, I here agree that E. cretacea is a pan-kinosternoid and therefore discuss it elsewhere (see Joyce and Bourque 2016). Finally, although Tullochelys montana Hutchison, 2013 from the early Paleocene of Montana was recently described as a new species of pan-chelydrid, I tentatively regard this as a pan-kinosternoid and therefore discuss it elsewhere as well (see Joyce and Bourque 2016).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although the available character evidence is conflicting, I here agree that E. cretacea is a pan-kinosternoid and therefore discuss it elsewhere (see Joyce and Bourque 2016). Finally, although Tullochelys montana Hutchison, 2013 from the early Paleocene of Montana was recently described as a new species of pan-chelydrid, I tentatively regard this as a pan-kinosternoid and therefore discuss it elsewhere as well (see Joyce and Bourque 2016).…”
Section: Introductionmentioning
confidence: 63%
“…Similarly, the Late Cretaceous (Maastrichtian) Emarginachelys cretacea Whetstone, 1978 was originally described as a pan-chelydrid (Whetstone 1978b) but was later reinterpreted to be a pan-kinosternoid, although an explicit rationale was not provided for this assessment (e.g., Meylan and Gaffney 1989;Holroyd and Hutchison 2002;Holroyd et al 2014). Although the available character evidence is conflicting, I here agree that E. cretacea is a pan-kinosternoid and therefore discuss it elsewhere (see Joyce and Bourque 2016). Finally, although Tullochelys montana Hutchison, 2013 from the early Paleocene of Montana was recently described as a new species of pan-chelydrid, I tentatively regard this as a pan-kinosternoid and therefore discuss it elsewhere as well (see Joyce and Bourque 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Plastral scutes.-Testudinoids are unique among extant turtles by possessing paired gulars, humerals, pectorals, abdominals, femorals, and anals (Hutchison and Bramble, 1981), in contrast to extant chelydrids and kinosternoids, which possess intergulars, but lack pectorals (Joyce, 2016;Joyce and Bourque, 2016). A recent phylogenetic analysis of Americhelydia with focus on Chelydroidea (i.e., the clade consisting of Chelydridae and Kinosternoidea) concluded that the lack of pectorals is a synapomorphy of Chelydroidea, but that pectorals were secondarily reacquired within this clade, for instance in the Paleocene dermatemydid Agomphus pectoralis (Cope, 1868) (Lyson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Kinosternon are relatively sparse (Bourque, 2012;Cadena, Jaramillo, & Paramo, 2007). The fossil record indicates that by the early to middle Miocene, Kinosternon existed across North America (Bourque, 2012(Bourque, , 2015Holman, 1998;Joyce & Bourque, 2016). Kinosternon were Multiple modeling approaches exist for evaluating how the distribution of organisms may change through time (Bakkenes et al, 2002;Huntley et al, 1995;Matthews et al, 2011).…”
Section: Despite Their Widespread Distribution Fossil Examples Ofmentioning
confidence: 99%
“…Despite their widespread distribution, fossil examples of Kinosternon are relatively sparse (Bourque, ; Cadena, Jaramillo, & Paramo, ). The fossil record indicates that by the early to middle Miocene, Kinosternon existed across North America (Bourque, , ; Holman, ; Joyce & Bourque, ). Kinosternon were present in Central America by at least the early Pleistocene (Cisneros, ), and South America by the late Pleistocene (Cadena et al., ).…”
Section: Introductionmentioning
confidence: 99%